2012
DOI: 10.4067/s0718-95162012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of temperature stress by nutrient management in crop plants: a review

Abstract: The burgeoning population of world is expected to reach about 9-10 billion by the end of year 2050. Due to this rapidly increasing population, food productivity is decreasing. Temperature induced stress is an important environmental factor that influences the growth and development of plants. Both low and high temperatures affect plant growth and development at whole plant level, tissue and cell level and even at sub-cellular level. Temperature variation may affect morphology, anatomy, phenology and plant bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
223
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(232 citation statements)
references
References 144 publications
5
223
1
3
Order By: Relevance
“…It is well known that crop growth rates are significantly reduced by temperature stresses as results of a decrease in metabolic processes and photosynthesis (Sharkova, 2001;Wise et al, 2004;Waraich et al, 2012), shoot and root growth inhibition, and leaf senescence (Vollenweider and Gunthardt-Goerg, 2005), however the growth reduction in the present study was only observed at low temperature, and this differed from the result of our previous study with lettuce (submitted). An extra-supply of minerals to promote tomato growth did not have any effect at both low and high temperature stresses (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…It is well known that crop growth rates are significantly reduced by temperature stresses as results of a decrease in metabolic processes and photosynthesis (Sharkova, 2001;Wise et al, 2004;Waraich et al, 2012), shoot and root growth inhibition, and leaf senescence (Vollenweider and Gunthardt-Goerg, 2005), however the growth reduction in the present study was only observed at low temperature, and this differed from the result of our previous study with lettuce (submitted). An extra-supply of minerals to promote tomato growth did not have any effect at both low and high temperature stresses (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…This damage to the intracellular membranes can also affect respiratory activity in mitochondria and cause a breakdown of pigments that might affect carbon fixation ability in the chloroplast (Scandalios 1993 O +O 2 ) and glutathione peroxidase (GPXs: 2glu-tathione + polyunsaturated fatty acid (PUFA)-OOH⇔glu-tathione reductase (GSSG) + PUFA + 2H 2 O), and it has been found that during acclimation, plants increase their stress-related proteins, which improve both the levels and activities of antioxidant enzymes. The antioxidants scavenge the ROS, decrease the photo-oxidation and preserve chloroplast membrane integrity and thereby help to increase the rate of photosynthesis (Waraich et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that the nutritional status of plants affects the ability to adapt to adverse environmental conditions (Waraich et al, 2012), meaning nutrients also act to attenuate abiotic stresses (Tahir et al, 2011) in the strutural integrity of plants and are the key to physiological processes such as photosynthesis, osmotic regulation and enzyme activation (Waraich et al, 2011).…”
Section: Resultsmentioning
confidence: 99%